Non‐convulsive epilepsy with acute‐onset and short‐lasting repeated fatigue attacks: A case of 30‐year‐old man. (28th February 2022) - Akimoto, Takashi; Kobayashi, Tadashi; Maita, Hiroki; Osawa, Hiroshi; Kato, Hiroyuki
Abstract: A 30‐year‐old man was referred to our department because of repeated acute‐onset and short‐lasting fatigue attacks, which occurred from 3 months before the referral. He had no abnormal findings in blood tests, electrocardiogram (including 24‐ h monitoring), or head MRI (including angiography). His vital signs were unremarkable, and his physical examination revealed no abnormal findings. Detailed history‐taking with closed‐ended questions revealed the occurrence of tingling sensation from the right fingers as the aura before his attacks. Electroencephalography was performed, which revealed focal epilepsy. Levetiracetam resolved his symptoms. Physicians could consider non‐convulsive epilepsy as a potential cause of repeated acute‐onset and short‐lasting fatigue attacks of unknown etiology after underlying conditions, such as metabolic diseases, have been ruled out.